2021
DOI: 10.22630/aspe.2021.20.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Households Savings and Financial Behavior in Relation to the Ability to Handle Financial Emergencies: Case Study of Kosovo

Abstract: To reflect the financial situation of households, especially for emergencies, the main purpose of this research is to analyze financial behavior in relation to savings. This research explains the interaction of minimum savings rules and committed forms of saving, which means that the use of personal budgets depends on financial behavior due to insecurity and the financial situation of families. The research is consistent with some empirical findings on financial behavior in relation to savings, which affect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…The various research studies conducted in the fields of climate change, sustainable finance, and budgeting were presented for the global economy, so these studies shed light on the key elements of individuals' expenses that are influenced by climate change, including food, beverages, housing, consumer goods of households (Lulaj et al, 2021). Regarding financial stability in a global economy (Cicen, 2023), it was emphasized that weak institutions can exacerbate financial shocks.…”
Section: Discussionmentioning
confidence: 99%
“…The various research studies conducted in the fields of climate change, sustainable finance, and budgeting were presented for the global economy, so these studies shed light on the key elements of individuals' expenses that are influenced by climate change, including food, beverages, housing, consumer goods of households (Lulaj et al, 2021). Regarding financial stability in a global economy (Cicen, 2023), it was emphasized that weak institutions can exacerbate financial shocks.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the income is irregular, and savings is one of the crucial sources in every situation for all households. (Lulaj et al, 2021), (Jin et al, 2021), (S. Ismail et al, 2018), (Shin & Kim, 2018), (Magendans et al, 2017) research indicated that savings play an important role in emergencies and significant contribution to financial wellness. (Gjertson, 2016) the study found that savings are a kind of insurance of low-income households which protects against hardship.…”
Section: Savings Behavior As a Mediatormentioning
confidence: 99%
“…Previous studies on farmers' education and its role in their decisions or behavior in Kosovo disregard financial literacy (Zeqiri et al, 2019), whereas studies regarding financial (il)literacy in Kosovo focused on other sectors or social groups. For instance, Lulaj et al (2021) analyzed Kosovo households' savings and financial behavior related to financial emergencies. Another study highlights the role of competence in mathematics in achieving financial mathematical literacy knowledge (Yildirim and Vardari, 2020).…”
Section: Introductionmentioning
confidence: 99%